Culture, money attitudes and economic outcomes - Caroline Henchoz; Tristan Coste; Boris Wernli (Swiss Journal of Economics and Statistics, 2019)
Using novel survey data, we examine attitudes towards money and to what extent they affect economic outcomes in Switzerland. We find that three main types of attitudes towards money co-exist: the prestige and power attitude, the money management attitude and the goal-oriented attitude. The distribution of these attitudes differs across Switzerland's linguistic regions; all of them are more significant in the French-speaking part, compared to the German- and Italian-speaking parts of Switzerland. Attitudes towards money shape financial behaviour, but the relationship varies depending on the type of financial behaviour. Culturally shaped attitudes to money are mostly linked with indebtedness; a finding that could help design better financial literacy programmes.
Keywords: A13; A14; D14; D83; I29; 330; Social values; Culture; Personal finance; Money; Education; Savings; Indebtedness